Efficient biodegradation of Congo red dye using fungal consortium incorporated with Penicillium oxalicum and Aspergillus tubingensis - Thakor, Rashmi; Mistry, Harsh; Tapodhan, Krunal; Bariya, Himanshu (Folia microbiologica, 2022)
A novel approach had been carried out to develop fungal consortium, namely, RH-2, containing two marine procured fungal isolates in order to evaluate biodegradation of recalcitrant diazo dye Congo red. The fungi were isolated from the seacoast of Diu, India. According to the ITS sequencing, the strains were identified as Penicillium oxalicum (DS-2) and Aspergillus tubingensis (DS-4). Discs of 12 mm were cut out from the edge of both the fungal isolates (DS-2 and DS-4) and inoculated in flasks consisting of potato dextrose broth with 100 mg/L Congo red for the development of fungal consortium RH-2. The degradation by the fungal consortium RH-2 was more effective than the fungal monocultures DS-2 and DS-4 with the respective degradation reaching 97.15 ± 0.15%, 68.96 ± 0.09%, and 29.96 ± 0.21% in addition of yeast extract (1% w/v) within 12 h. The influence of dextrose (1% w/v), yeast extract (1% w/v), pH 5, and salt concentration (1% w/v) enhanced the degradation potential of fungal consortium RH-2. The maximal degradation was correlated with the production of laccase (12.498 ± 0.21 U/mL) and manganese peroxidase (10.314 ± 0.25 U/mL). The catabolism of Congo red was confirmed by UV-Visible spectroscopic analysis (Congo red λ-max = 499 nm) and ATR-FTIR spectroscopic analysis. The filtrates obtained after Congo red degradation were also evaluated for microbial toxicity against bacteria (Bacillus haynesii) and phytotoxicity analysis on plant seed (Trigonella foenum) which revealed that the filtrate acquired after the treatment of Congo red by fungal consortium RH-2 was less toxic than the original dye in nature. A novel aspect is determined by the evidence of mutualistic interaction between two different fungi for the rapid decolorization and degradation of dye providing a prospective of utilizing the developed consortium RH-2 as a cost-effective approach in textile wastewater treatment for cleaner environment.
Keywords: Phytotoxicity; Kongo červeň; biodegradace; Congo Red; houby; azosloučeniny; Aspergillus tubingensis; Coloring Agents; Microbial toxicity; Penicillium; Fungi; Azo Compounds; Aspergillus; prospektivní studie; Prospective Studies; barvicí látky; Biodegradation, Environmental; Azo dyes; Laccase; Penicillium oxalicum